Pores of Arctica islandica shells. - Nils Höche (10204233); Eric O. Walliser (10204236); Niels J. de Winter (3358778); Rob Witbaard (549727); Bernd R. Schöne (8187015) (2021)
(A-C) Pores viewed on an untreated, fractured surface of a hinge plate. Insets in (A) and (C) depict an overview of the fractured shell. Yellow crosses within the insets denote the location of the respective images. (B,C) Higher magnification reveals the presence of shriveled organic envelopes (Org.) surrounding the partially void pores. (D-G) Pores viewed in a polished hinge surface after oxidation of the organic matter by immersion in 10.5% H 2 O 2 for 20 minutes. Direction of growth is to the right. (D) Pores were aligned with their longest axis parallel to the growth front, as shown here near an annual growth line (black dashed line). (E) A pore filled with co-aligned, fibrous particles facing the same direction. (F,G) Pores partially filled with granular, spherical particles and remnants of organics.